Personalized multichannel transcranial direct current electrical stimulation (tDCS) in drug‐resistant epilepsy: A SEEG based open‐labeled study - Fabrice Bartolomei; Maëva Daoud; Megane Delourme; Sophie Tardoski; Julia Makhalova; Eya Bourguiba; Samuel Medina Villalon; Stanislas Lagarde; Fabrice Wendling; Giulio Ruffini; Ricardo Salvador; Francesca Pizzo; et al. (Epilepsia Open)
Abstract Objective To evaluate the effects of personalized multichannel tDCS on seizure frequency, severity, quality of life, and psychiatric comorbidities in patients with drug‐resistant focal epilepsy. Secondary goals include assessing the safety and feasibility of this approach. Methods This open‐label pilot study involved 16 patients with drug‐resistant focal epilepsy. Patients underwent 3 cycles of personalized multichannel tDCS over 6 months, targeting the EZ defined by stereoelectroencephalography (SEEG). Each cycle consisted of five consecutive days of tDCS, with two daily sessions of 20 min each. The primary endpoint was a reduction in seizure frequency, with secondary endpoints addressing quality of life (QOLIE‐31 scores), seizure severity (NHS3 scores), and psychiatric comorbidities (NDDI‐E and GAD‐7 scales). Results Across all participants, a statistically significant 20% reduction in seizure frequency was observed (p = 0.044). Six patients (37%) were identified as responders (≥50% seizure reduction), with one achieving seizure freedom. The mean seizure reduction among responders was 68%. Significant improvements were noted in overall quality of life (QOLIE‐31, p = 0.009), with greater benefits for patients with poorer baseline scores. No overall significant changes were observed in depression, anxiety, and seizure severity scores, though individual variability was noted. The treatment was well tolerated, with mild adverse events, primarily skin‐related. Significance Personalized multichannel tDCS shows promise as a noninvasive therapeutic option for drug‐resistant focal epilepsy, with benefits in seizure reduction and quality of life. Although results were variable, the method's safety and feasibility support further exploration through randomized controlled trials to refine protocols, better select potential responders' patients, and validate findings. Plain Language Summary This study tested a personalized brain stimulation technique called tDCS in people with difficult‐to‐treat epilepsy. The treatment led to fewer seizures in some patients and improved their quality of life. The approach was safe and caused only mild side effects. These results suggest that this type of noninvasive brain stimulation may be a helpful new option for people who do not benefit from medication or surgery.